Antimalarial drug resistance and drug discovery: learning from the past to innovate the future - Liana Theodoridis; Teresa G. Carvalho (International Journal for Parasitology: Drugs and Drug Resistance)
The emergence and spread of artemisinin-resistant malaria over the past 15 years has led to a recent rise in global malaria cases and represents a major public health concern. Following decades of intense research efforts, the first malaria vaccine has been approved for clinical use in October of 2021. However, its 36 % efficacy highlights the ongoing need for novel and effective drugs to combat malaria. The majority of current antimalarials are derivatives of previous efficient compounds whilst new treatments with diverse chemical scaffolds have not been implemented into clinical practice since 1996. We argue that current research efforts should focus on developing novel chemical classes of compounds to help fight drug resistant malaria. Here we provide a comprehensive review of the antimalarial treatments currently in clinical use and discuss their significant limitations due to parasite drug resistance. Further, we discuss various approaches to antimalarial drug discovery and offer new perspectives on the topic, informing on current methods, both rarely and extensively used. Collating the most recent and up-to-date drug discovery strategies will not only maximise current global research efforts but will ensure all possible drug development avenues are trialed. This review provides innovative insights to circumvent antimalarial drug resistance and diversify malaria therapeutics.